2017
DOI: 10.1080/03007995.2017.1374936
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the performance of elastomeric pumps in practice: are we under-delivering on chemotherapy treatments?

Abstract: The performance of pumps varied, which affected nurse workload and patients' waiting-times. A smart system is an option to monitor the performance of pumps and to predict their accuracy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 22 publications
0
11
0
Order By: Relevance
“…16 An evaluation of the performance of elastomeric pumps in practice demonstrated that a proportion of patients were not receiving their planned doses mainly resulting from unfinished infusors being discarded. 24 Therefore, education is essential not only regarding adverse events that may result from the chemotherapeutic agents but also to teach appropriate use of the infusors including what to do if the infusions finish early, or late. There are also possible malfunctions for which protocols must be established, including in the unlikely event of leaks or the development of occlusions.…”
Section: Discussionmentioning
confidence: 99%
“…16 An evaluation of the performance of elastomeric pumps in practice demonstrated that a proportion of patients were not receiving their planned doses mainly resulting from unfinished infusors being discarded. 24 Therefore, education is essential not only regarding adverse events that may result from the chemotherapeutic agents but also to teach appropriate use of the infusors including what to do if the infusions finish early, or late. There are also possible malfunctions for which protocols must be established, including in the unlikely event of leaks or the development of occlusions.…”
Section: Discussionmentioning
confidence: 99%
“…Consequently, we conducted a two-phase study (Salman et al 2017) to observe and evaluat patients receiving home chemotherapy via elastomeric pumps (5FU infused via a 48 hour elastomeric pump) at three gastrointestinal medical day units (MDU).…”
Section: Delivering Chemotherapy At Home: How Much Do We Know?mentioning
confidence: 99%
“…Many studies have investigated drug stability in extended infusions in the outpatient parenteral antimicrobial therapy (OPAT) setting to ensure patients receive their intended dose of therapy . However, few studies have investigated the performance of the devices used or specifically any factors that may affect the total dose patients gets in this setting . These other factors may result in larger dose deficits for the patient than drug degradation, and must be understood to ensure best possible patient care.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4][5] However, few studies have investigated the performance of the devices used or specifically any factors that may affect the total dose patients gets in this setting. 6,7 These other factors may result in larger dose deficits for the patient than drug degradation, and must be understood to ensure best possible patient care.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation